Dynamic design of a magnetic-enhanced nonlinear energy sink. (15th February 2023) - Geng, Xiaofeng; Ding, Hu; Jing, Xingjian; Mao, Xiaoye; Wei, Kexiang; Chen, Liqun
Graphical abstract: Highlights: Non-contact magnetic force is proposed to limit NES vibrations to enhance reliability. Dynamic model of an oscillator coupled with a magnetic-enhanced NES is established. A magnetic-enhanced NES experimental platform was built and the theory was confirmed. The NES damping effect and the system reliability are improved by nonlinear magnetic force. Abstract: In order to improve the reliability of the nonlinear energy sink (NES), a nonlinear, non-contact magnetic force is proposed to limit the large vibration of the NES oscillator in this paper. Based on the magnetic force expression of permanent magnets, a dynamic equation of a linear oscillator (LO) equipped with the magnetic-enhanced NES (ME-NES) is established. The dynamic characteristics of the ME-NES are analyzed by approximate analytical and numerical simulations. Moreover, the experiment of the ME-NES is carried out to verify the theoretical results. The transient response and steady-state response of the LO with the ME-NES are investigated. The effects of nonlinear magnetic force, magnetic spacing, and magnetic field strength on the vibration of the NES oscillator and the LO are summarized. The results show that the limiting effect of nonlinear magnetic force is better than that of linear force. The vibration of the NES mass is evidently reduced, and the vibration suppression of the NES is significantly enhanced by the limitation of the nonlinear magnetic force. In a word, the proposed non-contact ME-NES is a reliable and efficient vibration reduction strategy, which is helpful to the design of the NES in engineering practice.